1986
DOI: 10.1002/neu.480170102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of octopamine, dopamine, and serotonin on production of flight motor output by thoracic ganglia of Manduca sexta

Abstract: Effects of biogenic amines on a centrally generated motor pattern in Manduca sexta were examined by pressure injecting nanomole to micromole amounts of octopamine, dopamine or serotonin into thoracic ganglia. Motor output was recorded extracellularly from a pair of antagonistic flight muscles and their motor neurons. The monoamines were found to alter production of a motor pattern that produces rhythmic wing flapping (10 Hz) and exhibits phase relationships similar to those in the flight pattern of intact moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
2
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(79 citation statements)
references
References 27 publications
(9 reference statements)
1
75
2
1
Order By: Relevance
“…In addition, the observation of partial loss of flight and associated physiology in DdCGAL4/UAS-TNT flies suggests that there is a requirement for DdCGAL4 neurons in the acute control of flight in adult Drosophila. This idea is supported by studies in Manduca sexta where biogenic amines have been shown to play a role in initiating, maintaining, and terminating flight behavior (Claassen and Kammer, 1986). At this stage, our experiments cannot directly address the requirement for the InsP 3 R in adult DdCGAL4 neurons.…”
Section: Gal4; Uas-tnt(in)mentioning
confidence: 77%
“…In addition, the observation of partial loss of flight and associated physiology in DdCGAL4/UAS-TNT flies suggests that there is a requirement for DdCGAL4 neurons in the acute control of flight in adult Drosophila. This idea is supported by studies in Manduca sexta where biogenic amines have been shown to play a role in initiating, maintaining, and terminating flight behavior (Claassen and Kammer, 1986). At this stage, our experiments cannot directly address the requirement for the InsP 3 R in adult DdCGAL4 neurons.…”
Section: Gal4; Uas-tnt(in)mentioning
confidence: 77%
“…Although acute application of OA is sufficient to elicit flight in a number of different insect preparations (Sombati and Hoyle, 1984;Claassen and Kammer, 1986;Stevenson and Kutsch, 1987;Duch and Pflueger, 1999), OA is not necessary for the initiation of flight in Drosophila but modulates flight initiation and maintenance. Even flies without any OA/TA-containing neurons can fly.…”
Section: Oa Is Not Required For Flight Initiationmentioning
confidence: 99%
“…In principle, both could be controlled by aminergic action on the CPG and/or on the fly's sensory system. It is well established that OA acts on the CPG in a number of insect species (Sombati and Hoyle, 1984;Claassen and Kammer, 1986;Stevenson and Kutsch, 1987), but central actions of TA are not known. OA has also been reported to increase the responsiveness of flight-associated sensory cells in insects (Ramirez and Orchard, 1990), and TA could conceivably reduce excitability of sensory neurons as Drosophila TARs activate chloride currents (Cazzamali et al, 2005).…”
Section: Sites Of Oa and Ta Actionmentioning
confidence: 99%
“…Serotonin affects the central nervous system as well as the sensory periphery and the neuromuscular junction (Evans, 1980;Mercer and Menzel, 1982;Claassen and Kammer, 1986;Nässel, 1988;Casagrand and Ritzmann, 1992;Erber et al, 1993;Menzel et al, 1999).…”
mentioning
confidence: 99%